Local Wisdom of Builders on The Quality of Making Concrete in Kendari City Southeast Sulawesi Province - Umar, Muhammad Zakaria (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2021)
In Kendari City, the concrete structure made by construction workers consists of: (a) concrete for the lower class; (b) concrete for middle society, and; (c) concrete for the upper community. The concrete is made with different sand material. This research is important to find out the method of making concrete made by construction workers in Kendari City. This research is intended to test the compressive strength and absorbency of the concrete made by construction workers in Kendari City. This study uses an experimental method with a quantitative approach. Based on laboratory test results that concrete material from 100% Unaha sand with the composition of 1 sack of cement: 4 barrel of unaha sand included in structural concrete. Concrete material from split stone and Pohara sand with a composition of 1 sack of cement: 4 barrel of Pohara sand : 4 barrel of split stone, concrete material from Unaha sand and Pohara sand with a composition of 1 sack of cement: 4 barrels of Unaha sand : 4 barrels of Pohara sand, concrete material from 100% Nambo sand with the composition of 1 sack of cement: 4 barrels of Nambo sand, concrete material from Nambo sand and Unaha sand with a composition of 1 sack of cement: 3 barrels of Nambo sand : 1 barrel of Unaha sand, and concrete material from Nambo sand and Sabulakoa sand with composition of 1 sack of cement : 3 barrels of Nambo sand : 1 barrel of Sabulakoa sand are included in non-structural concrete.